Real-time physical engine for floating objects with two-way fluid-structure coupling - Lazo, Marcos Gonzalo (2013)
A method to simulate graphic animations of objects floating in a water surface in real time is presented. The fluid is simulated by means of the Lattice Boltzmann method for the shallow-waters equations, and the movement of the floating objects is calculated with a Newtonian physical engine suitable for the mechanics of rigid bodies. A two-way interaction between the fluid surface and the object structures is achieved by providing inputs to the Newtonian engine representing buoyancy, drag and lift forces calculated from the solution of the Lattice Boltzmann scheme, which in turn is perturbed by displacement forces acting at the objects boundaries. The method is tested in animation scenes of boats and different adrift objects, showing excellent rendering rates in desktop computers.